VASYL STEFANYK AND EXPRESSIONISM IN THE UKRAINIAN LITERATURE OF THE 1920TH - Movchan, R. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article explores the reception of works of Vasyl Stefanyk by criticism and literary studies of the 1920th, his expressionist contribution to the process of modernizing of Ukrainian literature of the period. The article also studies the adoption of European expressionist experience by Ukrainian literature through avant-garde painting, futurism, Les Kurbas theatre, contemporary cinema.